PENGARUH ROA, ROE DAN PBV TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Sitanggang, Rexsy Mardohot; Sitanggang, Karolin Gabrela; Situmorang, Ninda Rohani; Sihaloho, Rebecca Putri; Manalu, Lija Tanjung; Sirait, Dita Eka Pertiwi (Universitas Madura, 2025)
The divergent stock price movements of large-cap banks during the 2022-2024 economic recovery indicate a market anomaly that demands a re-evaluation of fundamental indicators' relevance. This study aims to examine the effect of Return on Assets (ROA), Return on Equity (ROE), and Price to Book Value (PBV) on banking stock prices listed on the Indonesia Stock Exchange during the 2022-2024 period . The research method employs a quantitative causal approach with a purposive sampling technique, yielding 10 sample companies with a total of 30 observations. Data analysis was conducted using panel data regression with the Random Effect Model assisted by EViews 13 software. The results show that ROA and PBV have a positive and significant effect on stock prices, while ROE has a negative and significant influence. Simultaneously, the three variables explain 77.76% of stock price variations. These findings validate signaling theory but highlight that investors are now more selective in responding to high-risk equity profitability.